Systematics of the southern African genus Ixia (Iridaceae). 3. Sections Hyalis and Morphixia - P. Goldblatt; J. C. Manning (Bothalia: African Biodiversity & Conservation, 2011)
A revised classification is presented for Ixia L., a southern African genus restricted to the winter rainfall zone of the western part of the subcontinent, in which the four sections Dichone (Salisb. ex Baker) Goldblatt & J.C.Manning, Hyalis (Baker) Diels, Ixia, and Morphixia (Ker Gawl.) Pax are recognized and diagnosed. The circumscription of sect. Hyalis is emended to include both short- and long-tubed species, mostly with four or more leaves with the uppermost not sharply differentiated from the lower. This contrast with sect. Morphixia, also with short- and long-tubed species, in which the entirely sheathing uppermost leaf (rarely upper two leaves) is distinct from the lower two or rarely three leaves, which have well-developed blades. We revise these two sections, recognizing 18 species in sect. Hyalis, including the two new species, I. linderi and I. recondita, and recognizing 31 species in sect. Morphixia, including the 11 new species, I. alata, I. cedarmontana, I. dolichosiphon, I. ecklonii, I. linearifolia, I. monticola (previously included in I. latifolia var. angustifolia), I. pavonia, I. parva and I. ramulosa (raised from varietal rank as var. parviflora and var. ramulosa respectively of I. latifolia), I. saundersiana and I. stenophylla (previously I. fucata var. filifolia). We also provide a new name, I. mollis for the illegitimate homonym I. flaccida. Lastly, we transfer I. purpureorosea from sect. Ixia to sect. Hyalis. We recognize eight informal series, three in sect. Hyalis and five in sect. Morphixia. With these changes and additions the genus Ixia now comprises 78 species.